2009
DOI: 10.3810/pgm.2009.03.1981
|View full text |Cite
|
Sign up to set email alerts
|

Case Report:Escherichia coliSeptic Shock Masquerading as ST-Segment Elevation Myocardial Infarction

Abstract: Elevated cardiac biomarkers in conjunction with electrocardiographic (ECG) changes are valuable in diagnosing acute coronary syndrome (ACS). Elevated troponin I (TnI), while commonly seen in ACS, can also occur in entities such as sepsis and pulmonary thromboembolic disease. Raised TnI levels in patients with sepsis result from various mechanisms, including hypoperfusion or direct extension of infection to cardiac tissue, and can also serve as an important prognostic indicator. Electrocardiographic changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Precordial ST segment elevation has been previously described in patients with extensive PE 2)3). However, similar ECG manifestations have been described in patients with severe sepsis and normal coronary arteries 4)5). In our patient, despite the absence of RWMA and significant enzyme increase, acute coronary syndrome, coronary vasospasm and acute myocarditis constituted the differential diagnoses, as coronary angiography and endomyocardial biopsy were not readily available.…”
supporting
confidence: 76%
“…Precordial ST segment elevation has been previously described in patients with extensive PE 2)3). However, similar ECG manifestations have been described in patients with severe sepsis and normal coronary arteries 4)5). In our patient, despite the absence of RWMA and significant enzyme increase, acute coronary syndrome, coronary vasospasm and acute myocarditis constituted the differential diagnoses, as coronary angiography and endomyocardial biopsy were not readily available.…”
supporting
confidence: 76%
“…However, it was also reported that ST-segment elevations were rare in septic shock patients in the setting of normal coronary angiography. In addition, the electrocardiographic changes during septic shock also include a loss of QRS amplitude, increase in QT interval, development of narrowed QRS intervals with deformed bundle branch blocks [ 34 ] and new-onset atrial fibrillation, especially in older septic shock patients [ 35 ].…”
Section: The Clinical Characteristics Of Simdmentioning
confidence: 99%
“…The SIMD can be accompanied by specific changes in the electrocardiogram (ECG), which can be very similar to those occurring during acute coronary syndromes [22], including ST segment depression or elevation, Q wave appearance, new left bundle branch block, peaked T wave, lenghtening of the QTc interval or positively J waves (Osborn wave) appearance [144]. The ECG may suffer temporary modifications, with an initial predominance of ST segment elevation followed by appearance of a Q wave.…”
Section: Diagnosismentioning
confidence: 99%